2018
DOI: 10.3329/bjp.v13i2.36201
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticoagulant and thrombolytic activity of Berberis orthobotrys in animal model

Abstract: <p class="Abstract">Fundamental to this research was the evaluation of anticoagulant and thrombolytic potential of Berberis orthobotrys using clotting time, prothrombin time and activated partial thromboplastin time performed at 2.5, 5, 10% concentration. Aqueous-methanol extract significantly (p&lt;0.05) increased the coagulation parameters both in human blood as well as in rabbit blood and exhibited the more salient effect on prolongation of these coagulation parameters at 10% concentration. Aqueou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The extract's in-vitro anticoagulant activity is measured by measuring the time it takes a blood sample to clot, also known as prothrombin time. Prolongation of Prothrombin time is used to assess an agent's anticoagulant activity because it indicates the blockage of the extrinsic clotting factor pathway, which includes factors V, VII, and X, all of which are generally activated by vitamin K [45]. In the current study, crude extracts showed a significant (*p<0.05, and ***p<0.001) and concentration-dependent increase in prothrombin time when compared to the control (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The extract's in-vitro anticoagulant activity is measured by measuring the time it takes a blood sample to clot, also known as prothrombin time. Prolongation of Prothrombin time is used to assess an agent's anticoagulant activity because it indicates the blockage of the extrinsic clotting factor pathway, which includes factors V, VII, and X, all of which are generally activated by vitamin K [45]. In the current study, crude extracts showed a significant (*p<0.05, and ***p<0.001) and concentration-dependent increase in prothrombin time when compared to the control (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…7). Because Coumarin can inhibit the activation of the abovementioned vitamin K-dependent clotting factors, the anticoagulant effect of the crude extract could be attributed to the presence of Coumarin in plant extract [45], and [46]. Furthermore, the plant extract is said to be rich in flavonoid and alkaloid compounds that exhibit anticoagulant activity by forming a complex with clotting factors to inhibit the conversion of prothrombin to thrombin and, as a result, prevent the conversion of soluble fibrinogen to insoluble fibrin clot [47], and [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation